Control Efficacy of Fungicides on Chinese Cabbage Clubroot under Several Conditions - Min-Yong Eom; Yong Ho Choi; Kyoung Soo Jang,; Su-Jung Jo; Jin-Cheol Kim; Gyung Ja Choi (Research in Plant Disease, 2011)
To develop the efficient screening methods for antifungal compound active to Chinese cabbage clubroot caused by Plasmodiophora brassicae, the control efficacy of three fungicides fluazinam, ethaboxam, and cyazofamid on the disease was tested under several conditions such as soil types, cultivars of Chinese cabbage, growth stages of the host, and inoculum concentrations. The in vivo antifungal activities of the fungicides on clubroot of two Chinese cabbage cultivars were hardly different. At 7- and 14-day-old seedlings, the fungicides were more effective to control of clubroot than at 21-day-old seedlings. In a commercial horticulture media soil (CNS), disease severity of untreated controls was higher and control activity of the fungicides was less than in a mixture of CNS and upland soil (1:1, v/v). Disease development of the seedlings inoculated with P. brassicae at 1.8×10(7) spores/pot to 1.1×10(9) spores/pot was almost same, but control efficacy of the fungicides was negatively correlated with inoculum dosages. To effectively select in vivo antifungal compound on Chinese cabbage clubroot, 14-day-old seedlings need to be inoculated with P. brassicae by drenching the spore suspension to give 1×10(8) spores/pot 1 day after chemical treatment. To develop clubroot, the inoculated plants are incubated in a growth chamber at 20℃ for 2 days, and then cultivated in a greenhouse (20±5℃) for four weeks.